Defining the entrepreneurial mindset and discussing its distinctiveness in entrepreneurship research. (23rd September 2021) - Hattenberg, Dagmar Ylva; Belousova, Olga; Groen, Aard J.
The entrepreneurial mindset (EMS) is an emerging concept within entrepreneurship research, but has yet to reveal its full potential. Its current understanding is still fragmented and intertwined with other concepts. The purpose of this paper is to develop a theoretically informed definition of EMS that is descriptively robust and conceptually distinct from other concepts. By analysing definitions and comparing EMS to other established entrepreneurship concepts we argue that EMS captures both the developmental (ability) and the volitional (willingness) aspects that allow an individual to sense and seize an opportunity. It is the combination of these two aspects that makes EMS unique and distinct from other concepts. We ultimately propose future research steps to advance the understanding of this important phenomenon across multiple contexts.